2019
DOI: 10.5430/wje.v9n4p65
|View full text |Cite
|
Sign up to set email alerts
|

Father Involvement in Education Predicates the Mental Health Status of Chinese Primary School Students

Abstract: Previous studies have shown that quality and the quantity of father involvement in education play an important rolein children’s development. The influence of father involvement in education on Chinese children's mental healthstatus still needs further study. To understand the present situation of father involvement in education and its impacton children's mental health, this study will concentrate on the impact of father involvement on the mental healthstatus of primary school students, This study surveyed 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In one of the studies, Önalan (2016) found that fathers started to change their roles from traditionalism to modernity and that they started to think child-centered, with an increase in the roles of model, dynamism, and emotional ties in addition to their leader, need-fulfilling, future-planning features. Besides, studies are showing that parents' expectations from the child shape the lives of children and affect their psychological health (Zhang et al, 2019(Zhang et al, , Öngider, 2013. Stating what kind of individual, they want their children to be as a father, the participants stated that the change in fathers' expectations from the child moved away from traditional roles.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…In one of the studies, Önalan (2016) found that fathers started to change their roles from traditionalism to modernity and that they started to think child-centered, with an increase in the roles of model, dynamism, and emotional ties in addition to their leader, need-fulfilling, future-planning features. Besides, studies are showing that parents' expectations from the child shape the lives of children and affect their psychological health (Zhang et al, 2019(Zhang et al, , Öngider, 2013. Stating what kind of individual, they want their children to be as a father, the participants stated that the change in fathers' expectations from the child moved away from traditional roles.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…In the United Kingdom, fathers' beliefs in positive parental involvement when the child was 9 months old and his creative play with a child when he or she was 5 years old was associated with lower risks of behavior problems among both boys and girls (Kroll et al, 2016). A study in Yancheng, China sampled 1669 primary school children and found that greater fathers' involvement contributed to better children's psychological adaptability and mental health, with more active fathers' involvement associated with a student being less sensitive and impulsive (Zhang, Wang, & Lu, 2019). These results support the social capital theory which posits that father–child interactions can promote children's well‐being.…”
Section: Theoretical Frameworkmentioning
confidence: 99%